Pengaruh Inflasi, Pendapatan Perkapita, Investasi Syariah terhadap Tingkat Konsumsi Rumah Tangga - Rizkie Ragilita; Imsar; Ahmadi Bi Rahmani (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
This study aims to analyze the influence of inflation, per capita income (GRDP), and sharia investment on household consumption levels in North Sumatra Province from an Islamic economic perspective during the period 2013 to 2023. The approach used is quantitative by utilizing secondary time series data obtained from the Central Statistics Agency (BPS) of North Sumatra Province. The annual data is converted into quarterly data for analysis using the Vector Error Correction Model (VECM) method. The results show that the three independent variables of inflation, GRDP, and sharia investment do not have a significant effect on household consumption in the short term. However, in the long term, all three have a significant influence. The Granger causality test indicates a reciprocal relationship between inflation and GRDP on consumption, as well as a causal relationship between sharia investment and GRDP and consumption. Among these three variables, inflation is predicted to be the dominant factor influencing household consumption in the future, with a contribution of around 60 percent.